Pemanfaatan Tools GWEF dan Kebijakan Akun Belajar ID untuk Meningkatkan Kompetensi Pendidik dalam Pembelajaran Kolaboratif, Komunikatif, dan Atraktif di SMP Negeri 1 Bangli - Keramas Pradnyana, Dewa Gede; Sudarsana, I Ketut (Jayapangus Press, 2024)
This research aims to determine the level of utilization of Google Workspace for Education Fundamentals tools in Sekolah Penggerak program at SMP Negeri 1 Bangli. The respondents for this research were all teachers at SMP Negeri 1 Bangli with a total of 34 respondents. The method used is a survey method with questionnaires and written interviews assisted by Google Form. The findings showed that the majority of respondents have used Belajar ID account both in learning activities and assessments in class with varying frequency, and even 2 respondents (5.88%) in their learning and assessment activities always (100%) use the account. although there was also 1 respondent (2.94%) who had not used it at all for certain activities at school. Respondents whose level of usage of the account is still relatively low (1% - 25%) certainly need more intensive and sustainable dissemination to strengthen respondents' understanding of the account. Meanwhile, respondents used the account with varying frequencies ranging from 1% to 99%. The majority of respondents indicated that the frequency of using the account was in the range of 76% - 90%. Findings also showed that the majority of respondents use the account for learning and assessment activities (67.65%). Google Classroom is a very popular application because 50% of respondents use this tool because the face-to-face display and learning management available in it are very similar to conventional learning models. In second place, Google Forms were used by 20.59% of respondents, in third place was Google Docs which was used by 17.65% of respondents, and in fourth place was Google Drive which was used by 11.76% of respondents.